2020
DOI: 10.1159/000505120
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapeutic Work in Palliative Care

Abstract: In palliative care, multi-professional teams work to improve and maintain the quality of life of terminally ill patients and their families. In this field, clinical psychologists and psychotherapists take on a broad variety of tasks that range from preventive and supportive to psychotherapeutic work. Even if the provision of palliative care frequently does not yet offer appropriate need-based care by psychologists and psychotherapists, developments to that effect are clearly noticeable. The aim of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(55 reference statements)
1
3
0
3
Order By: Relevance
“…The newly acquired knowledge about typical barriers and threats to the perception of safety in the home environment could serve as a basis for reducing possible fears and concerns through psychological interventions. 27 The present study further contributes to previous research showing that grievances in care and treatment can trigger patients' experience of unsafe practices. 28 A significant number of study participants felt unsafe as a result of their medical treatment.…”
Section: Discussionsupporting
confidence: 77%
“…The newly acquired knowledge about typical barriers and threats to the perception of safety in the home environment could serve as a basis for reducing possible fears and concerns through psychological interventions. 27 The present study further contributes to previous research showing that grievances in care and treatment can trigger patients' experience of unsafe practices. 28 A significant number of study participants felt unsafe as a result of their medical treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Considering a 10% drop-out rate, data were collected from 37 participants. http://www.e-jhpc.org patients or their family members takes approximately 50 minutes [16]. Prior experimental studies on the effects of education, music, or laughter therapy in South Korea [17][18][19] found that attitudes toward caring hospice patients became more positive after one session of an educational program providing information about hospice [17], anxiety was reduced after one session of music therapy (50 minutes) [18], and anxiety was reduced after one session of laughter therapy (60 minutes) [19].…”
Section: Study Participantsmentioning
confidence: 99%
“…Una de las prácticas más comunes en nuestro entorno son las intervenciones de cuidados paliativos. Se trata de una intervención multidisciplinar y holística (Von Blanckenburg y Leppin, 2018), focalizada en el manejo y alivio del dolor y otros síntomas biopsicosociales que la persona pudiera presentar (Gramm et al, 2020). Si bien los cuidados paliativos no pretenden adelantar la muerte de la persona, reconociendo esta como un proceso natural (Radbruch et al, 2020), su abordaje incluye prácticas que se ocupan de atender esta, entre las que se incluyen la sedación paliativa o terminal, destinada a controlar la sintomatología refractaria en la persona agonizante, y la limitación o adecuación del esfuerzo terapéutico (Cardona et al, 2010;Mishara y Weisstub.…”
Section: La Atención Humana Ante La Muerteunclassified
“…La persona que demanda la eutanasia suele encontrarse inmersa en un sufrimiento total, donde las consecuencias más visibles y orgánicas de la enfermedad terminal se acompañan de dificultades psicológicas, existenciales y sociales (Gramm et al, 2020). Una de cada tres personas en situación terminal sufre síntomas notables de ansiedad o depresión (Rosenfeld et al, 2017) y la mayoría puede presentar otros síntomas psicológicos en un umbral al menos subclínico.…”
Section: La Eutanasiaunclassified
See 1 more Smart Citation